A Study of the Iranian Economic Growth by Using the Balance of Payments Constrained Growth Model (European Journal of Marketing and Economics, 2024)
This study is conducted aimed at investigating the Iranian economic growth based on the balance of payments constrained growth (BPCG) model. In contrast to the view of classical models that consider the economic growth to be related to supply-side in the economy, this model holds that the economic growth is dependent on demand-side in the economy, stating that the demand growth is inhibited by balance of payments deficit, and thus, it constrains achieving a higher economic growth rate. To investigate the model mentioned, the data on Iran’s non-oil export growth and non-oil GDP growth over the period 1980–2017 are analyzed using the Granger causality test and Auto Regressive Distributed Lag (ARDL) method. Results indicated that there was a long-run relationship between the non-oil economic growth and the non-oil export growth, and that the economic growth increased by 0.54% with a 1% increase in the non-oil exports. So, based on the above model, the need to pay attention to the non-oil exports to achieve a sustainable economic growth is confirmed.
Keywords: Balance of Payments Constrained Growth Model, Economic Growth, Thirlwall’s Law.